PENGARUH PEMBIAYAAN MURABAHAH DAN SUKU BUNGA BI TERHADAP PENDAPATAN MARGIN MURABAHAH PERBANKAN SYARIAH - Sindy Silvya Rosa; Mia Kusumawaty (Jurnal Akuntansi dan Keuangan (JAK), 2019)
The research objective was to determine the effect of murabaha financing and interest rate BI to Revenue Margin On Islamic Banking simultaneously and partially. This type of research is associative research. The data digunakanadalah secondary data, where the data is murabaha financing resources and Bank Indonesia interest rate and margin murabaha year 2011-2015 at six banks listed in Indonesia. Data collection techniques in this study is documentation. Data analysis techniques used in this research is qualitative analysis techniques. The analytical method used in this research is multiple linear regression analysis. The results of this study showed that simultaneous Murabahah Financing and Interest Rates Bank Indonesia influence Revenue Margin Murabaha Islamic Banking in Indonesia. Partially Financing Murabahahm significant effect on Income Margin Murabaha Islamic Banking in Indonesia, while the interest rate of Bank Indonesia partially no significant effect on Income Margin Murabaha Islamic Banking in Indonesia